The effect of the contrastive training using weights and plyometrics on the development of muscular ability and Extension for Handball Players - Idris, Reda Khodja; Bloufa, Boujamaa; Mokrani, Djamel (Journal of Education, Health and Sport, 2018)
We have tried through this research to work on raising the level of handball in our country, for the successful and good process of training and upgrading the training process by guiding the trainers in the right gallery and the scientific competence in modern training with the use of modern means to raise the level of players. From all aspects and focus on work With the smaller groups, who are the basis for ensuring the promising future of handball.Thus, we conducted this field research on the Juniors category for the Western Regional Handball Championship and applied a training method by proposing training contents for both weight and biometric training, in order to develop muscle strength and improve the players. To verify the hypotheses of the research, the researcher adopted his study on the experimental method. The experiment was applied to a sample of the players from the western regional handball teams of the Junior category where they were divided into experimental sample and control sample. The study concluded that "training with resistors biometrics" has a positive effect on the development of muscular ability and upgrading of handball players.